An Analysis on Students’ Substance Error in Writing Descriptive Texts - Supiani Supiani (Universitas Hamzanwadi, 2018)
This study aims to describe students’ substance errors especially the use of punctuation in writing descriptive texts. The present researcher used descriptive qualitative method in this study. It was conducted in English study program at the second semester of Hamzanwadi University. There were twenty students of C class chosen randomly to be participants. The data were collected by asking the participants to write an essay about descriptive text and asking the participants to fill some questionnaires. The participants’ work sheets and the questionnaires were analyzed to find out the common errors in using punctuation. The analysis showed the most dominant error were (1) the students omitted the use of comma that was 37,77%; (2) errors in using comma was 31, 11%; (3) error in using period that was 20%; (4) students omitting period that was 6, 66%; and (5) students omitted the use of apostrophe that was 4, 44%.